Simulation to Determine The Amount of Fan Rotation on a Cooling Machine Using The Fuzzy Logic Method - Afrizal Hasan Nasution (Bahasa Indonesia, 2020)
This Fan Rotation Simulation Application on Cooling Machines with Fuzzy Logic is an application that can simulate the fan rotation process based on the input voltage and temperature given by the user. In carrying out this simulation, this application uses a stress index with a category of small, medium, medium, high or higher. Temperature index with categories cooler, cooler, warmer, warmer and hotter. While the fan speed index uses the very slow, slow, rather fast, fast and very fast categories. This system can analyze the amount of fan rotation in RPM (Rotation Per Minute) automatically based on the input voltage and temperature and is equipped with a graphic facility that displays the simulation results of fan rotation, namely temperature graphs and fan rotation graphs. However. The designed system is equipped with fan rotation speed animation, to simulate fan rotation in the temperature range of -50 C.